The project of the Baron de Hirsch: Success or failure? - Edgardo Zablotsky (Universidad del Centro de Estudios Macroeconómicos de Argentina (UCEMA), 2005)
In 1891, Baron Maurice de Hirsch founded the Jewish Colonization Association (J.C.A.), through which he would manage a gigantic social welfare project concerning the immigration of thousands of people from the Russian Empire towards Argentina, and their settlement in agricultural colonies. In this paper, we evaluate the result of this project, which is generally qualified as a failure by historians on the subject. We hold an alternative hypothesis, wholly opposed to this conclusion: if the social evaluation of the project were carried out, taking into account the externality it generated, the conclusion would be that the project was highly successful; even though its private evaluation ,which implicitly is the usually made evaluation, would lead to the conclusion that it was a total failure. This externality is reflected in the number of immigrants arriving in the country independently of the J.C.A., but who would have never come here were it not be for Baron de Hirsch's project, since it placed Argentina on the map of East European Jewry, in a world in which the dissemination of information was slow and deficient.
Keywords: I38; N96; 330; Externalities; Baron Maurice de Hirsch; Jewish Colonization Association